Salusin-β, a TOR2A gene product, promotes proliferation, migration, fibrosis, and calcification of smooth muscle cells and accelerates the imbalance of vasomotor function and vascular remodeling in monocrotaline-induced pulmonary hypertensive rats - Wang, Xingxing; Chen, Aidong; Hu, Ruihua; Zhang, Feng; Liang, Shuxin; Bao, Changlei; Liu, Xuanxuan; Tang, Haiyang; Han, Ying (Frontiers in Pharmacology, 2022)
Purpose: The hyper-proliferation, promoted migration, fibrosis and calcification of pulmonary arterial smooth muscle cells (PASMCs) play critical roles in pulmonary arteries (PAs) continuous contraction and vascular remodeling leading to elevated pulmonary arterial resistance and pulmonary hypertension (PH). In this study, we sought to ascertain the effects of a TOR2A gene product, salusin-β, on PASMCs proliferation, migration, fibrosis and calcification and pulmonary vascular remodeling in monocrotaline (MCT)-induced PH rats and its underlying mechanisms. Methods: Knockdown or overexpression of salusin-β in rats or PASMCs was performed through tail vein injection or cell transfection of virus. Right ventricular systolic pressure (RVSP) of rat was measured by right ventricle catheterization. Sodium nitroprusside (SNP) or acetylcholine (ACh)-induced dose-dependent relaxation was used to evaluate the vasodilatation function. Primary PASMCs were isolated from the PAs of control and PH rats. Results: The salusin-β protein expressions were significantly increased in PAs and PASMCs isolated from PH rats compared with control rats. Knockdown of salusin-β in rats decreased high K+ solution-induced contraction, RVSP and RV hypertrophy index, improved SNP or ACh-induced vascular relaxation of PAs, and relieved vascular remodeling and calcification of PAs from PH rats. Silencing salusin-β in PASMCs isolated from PH rats alleviated the proliferation, migration, fibrosis and calcification, as well as the NAD(P)H oxidase activity and reactive oxygen species (ROS) level. Overexpression of salusin-β exerted the opposite effects on vasomotor function and vascular remodeling, and PASMCs proliferation, migration, fibrosis and calcification. Conclusion: Increased salusin-β activity in PAs from PH rats contributes to PASMCs proliferation, migration, fibrosis and calcification, leading to the imbalance of vascular contraction and relaxation and vascular remodeling through stimulating the production of NAD(P)H oxidase derived ROS.